Dietary fiber intake and reduced risk of ovarian cancer: a meta-analysis - Zheng, Bowen (Nutr J, 2018)
BACKGROUND: Epidemiological studies regarding the association between dietary fiber intake and ovarian cancer risk are still inconsistent. We aimed to review the available evidence and conduct a dose-response meta-analysis to investigate the relationship between dietary fiber intake and ovarian cancer risk. METHODS: Relevant studies were identified by searching PubMed, EMBASE, and the Cochrane Library databases before August 2017. Studies that reported relative risk (RR) estimates with 95% confidence intervals (CIs) for the association between dietary fiber intake and risk of ovarian cancer were included. Random-effects models were used to combine the estimated effects extracted from individual study. RESULTS: Thirteen studies, with a total of 5777 ovarian cancer cases and 142,189 participants, met the inclusion criteria. The pooled multivariable RRs of ovarian cancer for the highest vs. the lowest category of dietary fiber intake was 0.78 (95% CI: 0.70, 0.88) with no evidence of heterogeneity (I(2) = 4.20%, P = 0.40). Our dose-response analysis also showed a significant inverse association between dietary fiber intake and ovarian cancer risk (an increment of 10 g/day; combined RR: 0.88; 95% CI: 0.82, 0.93). There was no evidence for a nonlinear association (P for nonlinearity = 0.83). CONCLUSIONS: This meta-analysis suggests a significant inverse dose-response association between dietary fiber intake and ovarian cancer risk. Further studies with prospective design that take account of more potential confounders are warranted to confirm this association.